2018
DOI: 10.1128/aac.00519-18
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genetic Commonality among Wildlife, Wastewater, Community, and Nosocomial Isolates of Escherichia coli Sequence Type 131 ( H 30R1 and H 30Rx Subclones) That Carry bla CTX-M-27 or bla CTX-M-15

Abstract: sequence type 131 (ST131) is currently one of the leading causes of multidrug-resistant extraintestinal infections globally. Here, we analyzed the phenotypic and genotypic characteristics of 169 ST131 isolates from various sources (wildlife, wastewater, companion animals, community, and hospitals) to determine whether wildlife and the environment share similar strains with humans, supporting transmission of ST131 between different ecological niches. Susceptibility to 32 antimicrobials was tested by disc diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
3
24
2
Order By: Relevance
“…Here, virotype C was predominant among clade C1, specifically C1-M27 subclade, as also reported recently from South-West England and Europe ( 17, 18 ). In contrast to several European studies which reported the virotype A as the dominated virotype among C2 clade ( 12 ), in our study virotypes E and F were found as the most common virotypes, representative of > 60% of the C2 clade strains (22 out of 34 strains). Clade C2 showed a heterogeneous population based on the carriage of hlyA virulence marker, as positive strains had higher rates of resistance genes content and consequently higher resistance phenotype to tobramycin and gentamicin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, virotype C was predominant among clade C1, specifically C1-M27 subclade, as also reported recently from South-West England and Europe ( 17, 18 ). In contrast to several European studies which reported the virotype A as the dominated virotype among C2 clade ( 12 ), in our study virotypes E and F were found as the most common virotypes, representative of > 60% of the C2 clade strains (22 out of 34 strains). Clade C2 showed a heterogeneous population based on the carriage of hlyA virulence marker, as positive strains had higher rates of resistance genes content and consequently higher resistance phenotype to tobramycin and gentamicin.…”
Section: Discussioncontrasting
confidence: 99%
“…Considering the virulence genes content, the ST131 clone can be categorized into 12 virotypes which are named from A to F ( 11 ). While the virotype C is reported as the most common virotype among ST131 clone, the other virotypes have not the equal distribution among ST131 population reported in studies from different continents ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that these "weak-promoter integrons" are "low-cost structures" in E. coli and their carriage influences the fitness of the pathogen (Lacotte et al, 2017). The "integron effect" is supported by the high-quality report of Jamborova et al (2018) who performed a comprehensive investigation of a large number of ST131 H30 isolates and found that virotype A was the most common variant among the highly resistant strains. However, they also tested the integron content of the isolates and unequivocally showed that, similarly to MDR K. pneumoniae, in their collection, the more virulent virotype A isolates carried significantly more type 1 integrons than the virotype C strains.…”
Section: The Virulence Component In Mdr E Colimentioning
confidence: 98%
“…Though virotype C strains of ST131 H30 strains remain most frequent a few groups reported a higher incidence for virotype A isolates (Olesen et al, 2014;Ludden et al, 2015;Jamborova et al, 2018). Virotype A strains harbor a somewhat greater virulence gene load compared with virotype C. This extra gene load is supposed to be associated with fitness cost, thus, the question arises how could these isolates exceed equally resistant or less resistant virotype C strains?…”
Section: The Virulence Component In Mdr E Colimentioning
confidence: 99%
“…Indeed, the antibiotic-susceptible isolates of B subclade that is the progenitor of C1 and C2 subclade isolates carry an IncF plasmid with a plasmid multilocus sequence typing (pMLST) type Fϩ:A-:Bϩ whereas the multidrug-resistant C1 and C2 subclade isolates carry plasmids with pMLST types Fϩ:Aϩ:Bϩ, notably F1:A2:B20 without CTX-M-15, and Fϩ:Aϩ:B-, notably F2:A1:B-with CTX-M-15 (15,16). Similarly, the C1-M27 isolates, belonging to the C1 subclade, are frequently associated with F1:A2: B20 replicons (12,17,18). Although C1-M27 and C1/H30R harboring the bla CTX-M-14 gene have an identical plasmid type (F1:A2:B20), C1-M27 has emerged in human fecal carriage and has a greater epidemiological impact than CTX-M-14-producing C1/H30R (10).…”
mentioning
confidence: 99%